2014
DOI: 10.1021/om501093s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Gold(I) Complexes of Dibenzotropylidene-Functionalized NHC Ligands (Trop-NHCs)

Abstract: Gold(I) complexes of dibenzotropylidene-functionalized N-heterocyclic carbene ligands (Trop-NHCs) have been prepared in order to investigate their structural features and to reveal possible interaction of the olefin-unit with the metal center. The precursor imidazolium chloride salts (R-1) were generated in a single step using N-substituted imida-zoles (R = H, Me, DiPP, Ad) and one or two equivalents of Trop-Cl generating unsymmetrically and symmetrically NHC-olefin hybrids. The structural parameters of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…This allows the identification of features such as catalytic pockets, or might allow for the origin of enantioselectivity to be identified for some catalysts. For example, as shown in Figure 5 for [AuCl(ITrop)], 35 both South East (SE) and North West (NW) quadrants are heavily hindered by the ligand (%Vbur = 62.2 and 44.7, respectively); thus, in catalysis, this ligand would allow substrates to approach preferentially from the South West (SW) or North East (NE) positions (%Vbur = 28.3 or 38.4, respectively). This journal is © The Royal Society of Chemistry 2016…”
Section: Steric Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows the identification of features such as catalytic pockets, or might allow for the origin of enantioselectivity to be identified for some catalysts. For example, as shown in Figure 5 for [AuCl(ITrop)], 35 both South East (SE) and North West (NW) quadrants are heavily hindered by the ligand (%Vbur = 62.2 and 44.7, respectively); thus, in catalysis, this ligand would allow substrates to approach preferentially from the South West (SW) or North East (NE) positions (%Vbur = 28.3 or 38.4, respectively). This journal is © The Royal Society of Chemistry 2016…”
Section: Steric Mapsmentioning
confidence: 99%
“…Another example of how steric maps can help us to better understand the steric environment around a metal centre can be seen for unsymmetrical complexes bearing bulky yet highly flexible Nsubstituent, such as Trop (Entries 3-5, Table 4). 35 There, it can be appreciated how the N-Trop substituent can easily adapt itself to the steric requirements of the complex, thanks to the free rotation around the CN bond. This can lead to complexes where the Trop group is perpendicular (Entries 3 and 5, Table 4) or parallel to the XY plane (Entry 4, Table 4).…”
Section: Scope and Limitationsmentioning
confidence: 99%
“…the 13 C{ 1 H} NMR spectra of [Ni(AuCl)2] and [Zn(AuCl)2], respectively, confirming the formation of the CNHC-AuCl bonds. 1,43 The parent mass peaks could also be observed in their MALDI-TOF(+) mass spectra at m/z = 1494.4 Da (m/z calc. for Ott 44 and Peris's 33 groups showed that the reaction between gold(I) complexes [(NHC)-Au-Cl] and acetylides (generated in situ through deprotonation of the corresponding terminal acetylenes with a base) afforded the desired complexes [(NHC)-Au-CC-R].…”
Section: Synthesis and Characterization Of Janus Bis(nhc) Gold(i) Chlmentioning
confidence: 99%
“…The corresponding [Au(NHC)(NTf 2 )] complexes were prepared, and their activity in the hydration of diphenylacetylene was evaluated. 138 Only the complex containing NHC-28 (trop/dipp) was able to promote this transformation; however, the activity was much lower than that of the related Au-IPr complex. 138 Togni and coworkers explored the properties of Ntrifluoromethyl benzimidazole-based NHCs (NHCs-29− 33).…”
Section: N-heterocyclic Carbene Ligandsmentioning
confidence: 99%
“…138 Only the complex containing NHC-28 (trop/dipp) was able to promote this transformation; however, the activity was much lower than that of the related Au-IPr complex. 138 Togni and coworkers explored the properties of Ntrifluoromethyl benzimidazole-based NHCs (NHCs-29− 33). 131 The TEPs of the N-CF 3 NHC ligands were higher (2058−2060.8 cm −1 ) than that of NHC-34 (2053.3 cm −1 ) and much higher than the values for IPr (NHC-1, 2051.5 cm −1 ) and SIPr (NHC-2, 2052.2 cm −1 ).…”
Section: N-heterocyclic Carbene Ligandsmentioning
confidence: 99%